Relación Sentido de Vida en Personas con ideación y/o comportamiento suicida: Revisión Sistemática - Natalia de Brigard Merchán (Perspectivas Metodológicas​)
This Systematic Review analyses the significance of finding or not a Meaning of Life, on People with suicidal behavior. This review included articles in Spanish, indexed on REDALYC, and Dialnet from 2015 to 2020, analyzed using PRISMA methodology on Health and Psychology areas.  29 studies were selected, for a total of 8,561 Persons.  The methods used in these articles were: 88% quantitative type, 48% descriptive design, and 88% of the data was collected through applied instruments.  Most studies find a significant relation (50% of studies) between Existential Vacuum and, 16,7% between suicidal risk and identify the Meaning of Life as a protective factor.